Changes in dominant weeds of wheat in a rice–wheat rotation system as affected by composted manure and straw amendments. Issue 2 (12th March 2021) - Duan, Yunhui; Zhang, Haiyan; Han, Min; Hong, Aimei; Li, Yong; Sun, Guojun; Gao, Pinglei; Sun, Yicheng; Ran, Wei; Shen, Jiahe; Shen, Xin; Wu, Chenyu; et al.
Abstract: A study was conducted to identify whether composted manure and straw amendments (replacement of a portion of chemical fertilizer [50% of the total nitrogen application] with composted pig manure, and straw return [all straw from the previous rice crop] combined with chemical fertilizer) compared with no fertilization and chemical fertilizer only would change the dominant species of wheat-associated weeds as well as influence their growth and seed yield in a rice ( Oryza sativa L.)–wheat ( Triticum aestivum L.) rotation system. The study was initiated in 2010, and the treatment effects on the species, density, plant height, shoot biomass, seed yield of dominant weeds, and wheat yields were assessed in 2017 and 2018. Fertilization significantly increased the height, density, and yield of wheat, as well as the shoot biomass of wheat-associated weeds, but decreased the weed species number. A total of 17 and 14 weed species were recorded in the experimental wheat fields in 2017 and 2018, respectively. The most dominant weed species were American sloughgrass [ Beckmannia syzigachne (Steud.) Fernald] and catchweed bedstraw ( Galium aparine L.), which made up more than 64% of the weed community in all treatments. When the chemical fertilizer application was amended with pig manure compost and straw return, the relative abundance of B. syzigachne significantly decreased, while the relative abundance of G. aparine significantly increased. The application of the chemical fertilizer-only treatment resulted in increases in the density, shoot biomass, and seed yield of B. syzigachne, while the composted manure and straw amendments applied together with chemical fertilizer led to significant increases in the density, shoot biomass, and seed yield of G. aparine . Consequently, further research on ways to promote greater cropping system diversity will be needed to prevent the selection of weed species that are adapted to a limited suite of crop management practices.